The Role of Media and Popular Culture in the Mis/Education of Adults - Elizabeth J. Tisdell; Patricia M. Thompson; Talmadge C. Guy; Jennifer Sandlin; Robin Redmon Wright (Adult Education Research Conference, 2008)
The purpose of this symposium is to explore multiple perspectives on the role of media in the education and mis-education of adults, and to consider how educators might draw on media in developing a critical public pedagogy.
Keywords: critical media literacy; popular culture; critical public pedagogy